The Influences of Professional Development, in Educative Mentoring, on Mentors' Learning and Mentoring Practices - Cooke, Deborah Mary (Auckland University of Technology, 2018)
Mentoring plays a significant role in the successful acculturation of Provisionally Certificated Teachers (PCT) in New Zealand and has been formally recognised and centrally funded as part of mentoring and induction programmes in schools since the mid 1980s. Despite this long standing commitment the mentoring experiences of beginning teachers continue to be of varying quality. Some reasons attributed to this are that time is not provided for the mentors to enact their role and mentoring professional development is not afforded to support and grow mentors. The quality of mentors is another issue, as it is not uncommon for mentors to be selected primarily according to their teaching prowess and length of service, rather than their knowledge of or ability to work well with adult learners. This is concerning when it is understood that good teachers do not necessarily make good mentors. With the intention of providing the best start for their PCTs, mentors frequently adhere to traditional mentoring methods centred around pastoral care, the transmission of teaching knowledge, technical assistance and problem solving led by the mentor. Instead, what is needed are educative mentors who, in collaboration with their mentee, adroitly design a mentoring programme that furthers the PCTs’ understanding and application of teaching pedagogy while maintaining a focus on the achievement of students and fostering the unique professional identity of each mentee. Research suggests, however, that mentors do not innately shift from traditional mentoring to educative mentoring approaches and so professional development is frequently recommended to promote and support this transition. Despite this recommendation little research has been conducted into understanding what impact professional development has on how mentors learn or their mentoring practices. This realisation provided the impetus for this study which sought to explore the impact of collaborative professional development on the learning and mentoring practices of six mentors who mentor PCTs. Situated within an interpretivist/constructivist paradigm, and in keeping with the collaborative premise of the study, Participatory Action Research, along with focus group and semi-structured interviews, were the chosen qualitative methodology and data collection tools. The results from this small-scale study revealed that in a short time frame the mentors were able to trial various self-selected educative mentoring principles and change their thinking and actions about their mentoring beliefs and practices. The creation of disjuncture between mentors’ personal beliefs and new learning, along with opportunities for the social construction of knowledge and the implementation of focussed new learning as part of the mentors’ day-to-day mentoring work proved to be critical components that led to double loop learning for the mentors. A significant finding was also that the mentors’ learning was tightly bound to the learning of their mentees. As the mentors formulated goals that required them to change their mentoring approaches, they sought observable and measurable evidence of their effectiveness through the changes their PCTs made. The implication of this being that the mentors were reliant on external factors beyond their control rather than any intrinsic sense of growth to determine the extent of their own learning.
Keywords: Educative mentoring; Participatory Action Research; Mentor's learning; Professional development